Pengaruh Model TGT Berbantuan Media Quizwhizzer Terhadap Hasil Belajar Matematika Siswa Kelas V SD Kota Bengkulu - Miranda, Riza; Agusdiantia, Neza; Tarmizi, Pebrian (JURIDIKDAS, 2025)
This study aims to assess the impact of TGT model supported by quizwhizzer media on the mathematics learning outcomes of fifth-grade students in elementary school within cluster XII of Bengkulu City. The research utilizes a quantitative approach with Quasy Experiment design, specifically the Matching Only Pretest-Posttest Control Group Design. The study’s population cosists of fifth-grade students in elementary school of Cluster XII in Bengkulu City. a Cluster Random Sampling technique was employed to select the sample, which included students. From class VC of SDN 20 Bengkulu city as the experimental class and students of class VB SDN 20 Bengkulu city as the control class. The research instruments consisted of a pretest and a posttest, each containing 10 multiple-choice questions. Hypothesis testing of the test posttest data the experimental and control class show that the tcount value is 4,721 and the Sig (2-tailed) of 0.000 and the ttable distribution with a significance level (0,05) is 1,675, so the tcount (4,721 ) > ttable (1,675) and Sig. (2-tailed) is (0,000) < (0,005), it can be concluded that there is an influence of the TGT model assisted by quizwhizzer media on the learning oucomes in mathematics learning of fifth-grade students in elementary school within cluster XII in Bengkulu city.